Elections in the time of covid-19: the triple crises around Malawi's 2020 presidential elections. (31st May 2021) - Dulani, Boniface; Harris, Adam; Lust, Ellen; Ferree, Karen; Kao, Kristen; Ahsan Jansson, Cecilia; Metheney, Erica Ann
ABSTRACT: In June 2020, in the midst of the Covid-19 pandemic, Malawians went to the polls and voted to replace the incumbent government. Much like other natural disasters, the Covid-19 pandemic and accompanying economic and political shocks had the potential to shake voters' confidence in the government, reduce turnout, and/or reduce support for the incumbent if voters associated them with the ills of the pandemic. In this paper, we examine the extent to which the Coronavirus pandemic influenced Malawi's 2020 elections. We consider how fear of infection and economic distress affected citizens' trust and confidence in President Mutharika's government, their willingness to turn out to vote, and their choices at the polls using data collected pre- and post-Covid. We find that fears about the virus and its economic impact did influence trust and confidence in the government to handle Covid but had little to no effect on either abstention or vote choice.